THE ROLE OF SECONDARY MINERALS IN CONTROLLING THE MIGRATION OF ARSENIC AND METALS FROM HIGH-SULFIDE WASTES (BERIKUL GOLD MINE, SIBERIA) - Gieré R.; Sidenko N.V.; Lazareva E.V. (My University, 2003)
The role of secondary minerals in controlling the migration of As, Cu, Zn, Pb and Cd has been investigated in piles of high-sulfide waste at the Berikul Au mine, Kemerovo region, Russia. These wastes contain 40–45 wt.% sulfides and have been stored for approximately 50 a near the Mokry Berikul river. Sulfide oxidation generates acid pore solutions (pH=1.7) with high concentrations of SO42− (190 g/l), Fe (57 g/l), As (22 g/l), Zn (2 g/l), Cu (0.4 g/l), Pb (0.04 g/l), and Cd (0.03 g/l). From these solutions, As is precipitated as amorphous non-stoichiometric Fe-sulfoarsenates in the lower horizons of the waste piles. During precipitation of the Fe-sulfoarsenates, the concentration of Fe in these phases decreases from 34 to 21 wt.%, that of As increases from 11 to 22 wt.%, while the S content remains approximately constant (5.4–5.8 wt.%). Arsenic is also accumulated in jarosite-beudantite solid solutions (up to 8.4 wt.% As), which occur as inclusions in the amorphous Fe-sulfoarsenates. In efflorescent crusts on the surface of the waste pile, As co-precipitates with the Fe(III) sulfates copiapite (0.27 wt.% As) and rhomboclase (0.87 wt.% As). Zinc and Cu are incorporated primarily into Fe(II) sulfates, i.e. melanterite in the interior of the waste pile, and rozenite in the efflorescent crust. The Zn mineral dietrichite is also formed at the surface of the waste pile as a result of evaporation of pore solutions, and is the only Fe(II) sulfate containing detectable amounts of As (0.64 wt.%). Lead is mainly co-precipitated with minerals of the jarosite group, where the Pb content may reach 4.3 wt.%. Co-precipitation of toxic elements with sulfates and sulfoarsenates of Fe is shown to be a significant mechanism in controlling the concentration of heavy metals in pore solutions of high-sulfide mine wastes. Precipitation of secondary phases causes the formation of a hardpan layer with low permeability at a depth of 1–1.5 m below the surface of the waste pile. Rainwater accumulates above the hardpan horizons and slowly drains along these aquicludes to the bottom of the pile. Most of the rainwater evaporates during infiltration. This leads to formation of the described efflorescent sulfate crusts. Dissolution of these crusts during the next rain storm produces highly acidic surface waters (pH=1.1) rich in SO42− (30 g/l), Fe (18 g/l), As (0.24 g/l), Zn (0.12 g/l), Cu (0.04 g/l), Pb and Cd (0.002 g/l). During the warm (t>0 °C) period of the year, which lasts about 7 months, these surface waters transport a total of a few tens of kilograms of As and Zn, several kilograms of Cu, and a few hundred grams of Pb and Cd from the waste pile into the Mokry Berikul river. As a result, the concentrations of these metals in the river water increase by an order of magnitude, thus reaching levels close to, or exceeding the maximum values permissible for drinking water.